Complications of including physically challenged students in physical education class from the physical educator’s point of view - Husni, Jasser (Journal of Physical Education, 2017)
The aim of the study is to identify the complications of including physical challenged students in physical education class from the physical educators point of view in Jordan northern governorates (Arbid، Ajlon، Jersh). The researcher used a questioner to conclude the point of view of 153physical educators. The questioner consisted of 22 items divided into three axes (organizational obstacles، social obstacles، and physical obstacles). The results of the questioner showed that physical educators understudy considered physical challenged students in physical education class in all axes as well as the absence of significant statistical differences in gender، scientific qualification. The results also showed that there are differences due to experience in favor of the ones who are more experience